Antioxidant activity and composition of Clinopodium tomentosum in wet and dry extraction - Enríquez-Estrella, Miguel Angel; Serrano-Torres, Gabriela Joseth; Torres-Rodriguez, Silvia Hipatia; Cuadrado-Ayala, Dennis Gabriel (Revista Mexicana de Ciencias Agrícolas, 2025)
In ancient times, various plant species were used in traditional medicine due to their properties, being utilized in diverse processes, both in the food and pharmaceutical sectors. The purpose of this study was to characterize the bioactive components, specifically antioxidants and polyphenols, present in Clinopodium tomentosum in both dry and wet samples. An ultrasound-assisted extraction method was implemented to obtain the active compounds. Subsequently, the identification and quantification of the extracted compounds were performed using the FRAP (Ferric Reducing Antioxidant Power) and Folin-Ciocalteu assays. As a result of this process, it was observed that extraction from dry matter yields higher concentrations, with 1.49 mg L-1 of polyphenols and 1.27 mg L-1 of antioxidants, compared to wet extraction, which yielded concentrations of 1.39 mg L-1 of polyphenols and 1.04 mg L-1 of antioxidants. The characterization of Clinopodium tomentosum enabled the identification of its bioactive components, paving the way for future research on the identification of its phytochemical components and their potential application in both food and non-food industries.
Keywords: active principle; bioactive; extracts; phytochemicals